2019
DOI: 10.1002/elps.201900130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis of microvesicles in human serum for the evaluation of osteoporosis

Abstract: Osteoporosis is an emerging health issue worldwide. Due to the decrease of bone mineral density and the deterioration of skeletal microarchitecture, osteoporosis could lead to increased bone fragility and higher fracture risk. Since lack of specific symptoms, novel serum proteomic indicators are urgently needed for the evaluation of osteoporosis. Microvesicles (MVs) are important messengers widely present in body fluids and have emerged as novel targets for the diagnosis of multiple diseases. In this study, MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…There are several studies that have analyzed the quantitative proteome profiles and explored particular BMD-related proteins or genes based on peripheral blood monocytes (Shao et al, 2019; Zhang et al, 2016). Recently, a comparative proteomics analysis of serum microvesicles for the evaluation of OP was reported, and the authors found that Profilin 1 could differentiate those in the OP group from those in the ON and normal groups (Huo, Li & Qiao, 2019). Our study is the first to investigate plasma proteomic profiling in Chinese postmenopausal women with OP, ON, and normal bone mass using TMT and PRM approaches.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have analyzed the quantitative proteome profiles and explored particular BMD-related proteins or genes based on peripheral blood monocytes (Shao et al, 2019; Zhang et al, 2016). Recently, a comparative proteomics analysis of serum microvesicles for the evaluation of OP was reported, and the authors found that Profilin 1 could differentiate those in the OP group from those in the ON and normal groups (Huo, Li & Qiao, 2019). Our study is the first to investigate plasma proteomic profiling in Chinese postmenopausal women with OP, ON, and normal bone mass using TMT and PRM approaches.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have analyzed the quantitative proteome profiles and explored particular BMD-related proteins or genes based on peripheral blood monocytes (Shao et al, 2019;Zhang et al, 2016). Recently, a comparative proteomics analysis of serum microvesicles for the evaluation of OP was reported, and the authors found that Profilin 1 could differentiate those in the OP group from those in the ON and normal groups (Huo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Profilin 1 was further prevalidated in independent sample sets, which could be distinguished between the osteoporosis group, osteopenia group, and normal group ( p < 0.05). Their data indicated that the serum microvesicles proteome can be used for evaluation and diagnosis as important indicators of bone-loss disease [ 32 ]. In addition, Ming Chen and others from China 301 Hospital compared the protein profiles of plasma exosomes from 60 patients with osteoporosis, osteopenia, and normal bone mass, aiming to find potential new diagnoses.…”
Section: Evs As Potential Diagnostic Tool In Osteoporosismentioning
confidence: 99%